From Sportswashing to Cultural Changes and Positive Values - Moriconi, M. (Play the Game Conference 2025, 2025)
Sportswashing has become a fashionable concept when discussing the use of sport for political purposes, especially in the anglophone media. In 2022, the term increased in popularity as did its presence in public discourse, especially with the holding of the FIFA World Cup in Qatar. It even reached the social sciences where an incipient production of articles on the subject has emerged. Despite the prevalence of the term, there is almost no debate around the nature of the concept. Its definition is somewhat limited and contradictory, and its utility generates more doubts than certainties. Given this framework, this article presents a critical deconstruction of the concept by denoting the semantic contradictions, analysing the practices and the actors described by journalists and activists, and promoting a critical way of analysing how governments use sport. The presentation will be divided into 4 parts. In the first one, the efficient multi-actor sports strategy implemented by Gulf countries, with clear social, economic and political goals (Soyland and Moriconi 2022) will be explained. The second part will present an introduction and conceptualization of sportswashing. The third part presents 5 premises, based on the critical review of the scientific literature, why the concept is limited for political and social analysis: a) the concept is confined to restricted actors, b) it has been criticised for being discriminatory, c) it is ontologically pejorative and despotic, d) it presents a limited and/or erroneous logic of power and human action, c) and avoids the complex analysis of complicity in human action. The last part demonstrates how the political use of sport by countries that have been targeted by the concept of sportswashing, rather than washing the image or allowing the concealment of socio-political realities, what it does is to encourage and increase the scrutiny of international public opinion. In relation to this situation, the paper explains why it is a great opportunity to extrapolate positive values and generate profound cultural reforms.